Sustainable synthesis of samarium molybdate nanoparticles: A simple electrochemical tool for detection of environmental pollutant metol - Mutić Tijana; Stanković Vesna; Milikić Jadranka; Bajuk-Bogdanović Danica; Kalcher Kurt; Ortner Astrid; Manojlović Dragan; Stanković Dalibor (Journal of the Serbian Chemical Society)
This study focused on creating a highly effective sensor for detecting and quantifying the nitrogen-organic pollutant metol (MTL). For this purpose, samarium molybdate (Sm2(MoO4)3) nanoparticles were synthesized using an eco-friendly, organic solvent-free and cost-effective hydrothermal method. These nanoparticles were used as a modifier of carbon paste electrodes (CPE), showing exceptional catalytic efficiency. Electrochemical measurements revealed that the developed electrode facilitates electron transfer processes and enhances the catalytic response. The resulting Sm2(MoO4)3/CPE sensor exhibited a broad linear range of 0.1–100 and 100–300 μM of MTL, with low detection and quantification limits of 0.047 and 0.156 μM, respectively, at pH 3 in a Britton–Robinson buffer solution (BRBS) as the supporting electrolyte. The findings from the analysis of real water samples from various sources using this sensor were encouraging, suggesting that this method could offer a cost- -effective, rapid and sensitive sensor for ambient MTL monitoring.